VALUASI EKONOMI EKOSISTEM HUTAN MANGROVE DI DESA APAR, KECAMATAN PARIAMAN UTARA, KOTA PARIAMAN, PROVINSI SUMATERA BARAT - Rezi Junialdi; Yonariza Yonariza; Ardinis Arbain (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2019)
Mangrove forest in Apar village has not been maintained as a tourist spot until when the surrounding social community realises the function and benefits of the forest. Drought and exploitation for firewood cause the death of the plantation that threaten the forest sustainability. To manage and preserve the ecosystem, several efforts have been implemented, one of them is by quantifying environmental services provided by the mangrove ecosystem, commonly referred to as economic valuation. This valuation can be used as a reference in terms of strategic planning of coastal areas management to maintain the mangrove ecosystem sustainability. This study aims at (a) calculating the economic value of the mangrove forest in Apar village, Pariaman city, (b) analysing factors that influence obtained economic-benefits. The results of this study shows that the total economic value of mangrove forest in the area of 10.62 ha in Apar village is Rp950,486,837.58/year. The exsistent value has the highest value of Rp783,779,874.6/year. The direct use value is Rp89,520,000/year while the indirect economic value in the third place is Rp74,898,670.98/year and the option value is Rp2,318,292/year. The exsistence base on willingness to pay (WTP), namely income and education level, becomes the determining factors.